Efek Kava (Piper Methysticum) Sebagai Anestesi - Lasmaria Flora Roslinda Silaen; Matdhika Sakti; Ferianto Ferianto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Kava (Piper Methysticum) is a plant traditionally used in the South Pacific for its sedative and anxiolytic effects. Its active compounds, kavalactones, are known to have potential as natural anesthetics, with a mechanism of action similar to benzodiazepines and general anesthetics. This study aims to evaluate the effectiveness of Kava as an anesthetic through a systematic literature review and meta-analysis. Literature searches were conducted in PubMed, Scopus, and Cochrane Library using relevant keywords. Meta-analysis results indicate that Kava significantly enhances anesthetic effects compared to placebo, primarily through modulation of GABA-A receptors. However, further research is needed to determine the optimal dosage and long-term safety.